ANALISIS ASUHAN KEPERAWATAN PADA PASIEN GAGAL GINJAL KRONIK DENGAN PENERAPAN TERAPI PIJAT PUNGGUNG TEHADAP PENURUNAN KELELAHAN FISIK: ANALYSIS OF NURSING CARE IN PATIENTS WITH CHRONIC RENAL FAILURE WITH THE APPLICATION OF BACK MASSAGE THERAPY TO PHYSICAL FATIGUE - Saputra, Bayu; Tambunan, Gina (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2023)
Introduction: Chronic kidney failure is a disease that causes the function of the kidneys to decrease until they cannot perform their functions properly. Methods: The research method uses quantitative research with a quasi experimental one group pretest-posttest design. The respondents used in this application were 2 patients with chronic kidney failure. Data collection techniques used fatigue observation sheets, as well as standard back massage therapy procedures. Application is carried out once every 3 days, namely during the day. Result: The results of the application show the fatigue level score in the patient Mrs. On the first day of the pretest there were 37 heavy categories and on the third day of the posttest the results were 12 light categories. And to Mr. A obtained a fatigue level score on the first day of the pretest of 25 in the medium category. And on the third day of the posttest, it was found that 9 experienced a decline from moderate to mild. Conclusion: The application of back massage therapy in patients with chronic kidney failure has proven effective in overcoming the problem of physical fatigue, which is indicated by changes in the results of the score on the level of physical fatigue. This back massage therapy can be continued by the family when the patient's fatigue reappears, so that it can solve the patient's nursing problems.